Over-the-horizon link based on high-frequency pulsed CuBr laser - Gubarev F. A. Fedor Aleksandrovich; Li Lin; Degtyarev A. E. Andrey Evgenjevich; Shiyanov D. V. Dmitry Valeryevich; Klenovskii (Klenovsky) M. S. Miron Stanislavovich (2015, 2015)
Title screen